ANALISIS YURIDIS TERHADAP PENEGAKAN HUKUM TINDAK PIDANA KORUPSI TERHADAP PENENTUAN KERUGIAN KEUANGAN NEGARA (STUDI PUTUSAN NO.1596 K/PID.SUS/2013) - Erick Erick; Madiasa Ablisar; Sunarmi -; M. Ekaputra - (Ilmu Hukum Prima (IHP), 2021)
Returning losses from the proceeds of corruption will make the perpetrator unable to enjoy the results of his actions. This can be done by seizing certain items obtained or produced in a criminal act as a criminal in carrying out the principle of the life of the nation and state. Basically, state losses occur if the achievements received by the state are less than the money paid by the state. The research method in this thesis is a normative legal research method, namely by conducting library research namely research conducted by examining library materials, especially laws and legal literature relating to problems. The source of data used in this thesis is in the form of prier legal material and or secondary legal material that has to do with qualitative problems, namely what is obtained from research in the field is studied in a comprehensive and comprehensive manner. "State finances or economy" has been explained as discussed in Article 2 of Law Number 31 of 1999 jo Act Number 20 of 2001. Whereas the word "can" actually gives flexibility to the Prosecutor / Public Prosecutor does not have to prove an element of loss " financial / economic state "because corruption is a formal offense, namely the existence of criminal acts of corruption enough to fulfill the elements of corruption, enough to fulfill the elements of actions that have been formulated not by the emergence of consequences. The formulation of the provisions of Article 3 of Act Number 31 of 1999 in conjunction with Law 20 of 2001 is almost identical to the provisions of Article 1 paragraph (1) sub b of Act Number 3 of 1971. only difference is the provisions of Article 3 of Law Number 31 In 1999 jo Law No. 20 of 2001 included elements of "corporation" in it.